A Simple Method to Fabricate Hemocompatible Coating by Crosslinkable Biomimetic Bipolymer - Yang, Shan; Wang, Yanbing; Gong, Ming; Gong, Yongkuan (Asian Journal of Chemistry, 2014)
2-Methacryloyloxyethyl phosphorylcholine (MPC) and 3-(methacryloyloxy) propyltrimethoxysilane (TSMA) were used to synthesize the crosslinkable biomimetic copolymer PMT by the free radical copolymerization. The PMT82, the molar ratio 8:2 of MPC and TSMA in copolymer, was chosen as the coating material. It was dissolved in methanol and dip-coated on cover glass in order to obtain the biomimetic coating. The PMT coatings were fixed onto the glass substrate through heating in moisture atmosphere. The surface hydrophilicity, elemental composition, blood compatibility of the coatings were measured by dynamic contact angles, X-ray photoelectron spectroscopy, platelet adhesion and protein adsorption in vitro, respectively. The results indicated that the polymer coatings have been successfully immobilized onto the surface of cover glass, which improved the surface hydrophilicity of cover glass and granted it excellent blood compatibility. The biopolymer PMT will be a promising coating material, and the simple surface modification method will be useful in biomaterials field.